Knowledge and practice of breast self-examination: an integrative review (Research, Society and Development, 2020)
To identify which actions of the nurse in the early detection of breast cancer; check the limitations found by them to carry out these actions; and to identify the role of nurses regarding breast self-examination. This is an integrative literature review, which used the databases: MEDLINE, LILACS and BDENF. The search for the articles took place from September to October 2019 and the search terms were “Breast cancer”, “Self-examination”, “Tracking” and “Nurse”. Two themes were obtained: Knowledge of nursing professionals and women about the importance of performing breast self-examination to prevent breast cancer; Strategies used by nurses to encourage women about breast self-examination and raise awareness about breast cancer. The focus on breast cancer is important. Educate women to perform breast self-examination, as well as to carry out actions and strategies that raise awareness and guide them on this topic, allowing early diagnosis.